INTERIOR DESIGN OF NUSANTARA ARCHITECTURE MUSEUM WITH ANALOGICAL DESIGN APPROACH IN UBUD - Salsabila Karnada, Haura
Indonesia is a country with 38 provinces that have various kinds of cultural heritage, one of which is traditional architecture. Traditional architecture is the embodiment of building and designing techniques by a group of people who live in an area with certain beliefs. One form of traditional architecture that is owned by every region and province in Indonesia is traditional house. Indonesian traditional houses have various forms, histories and philosophies. However, the majority of traditional houses from various regions in Indonesia were built with a cosmological background that tends to be the same, which is the division of the 3 realms of the world. Unfortunately, traditional houses are now increasingly difficult to find due to the changing techniques to build houses using modern methods. As a result, it is quite difficult to introduce Indonesian traditional architecture or traditional houses to foreign tourists or the nation's next generation. Ubud District in Gianyar Regency, Bali is one of the famous destinations for foreign and local tourists because it is famous for its various artistic, cultural and natural tourist destinations. Therefore, the nusantara architecture museum in Ubud that contains traditional houses from Indonesia is built to introduce Indonesian cultural heritages, as well as promoting other areas in Indonesia which are rich in culture and local wisdom.